Effects of genotype by environment interaction on agronomic and functional flour properties among cassava genotypes targeted for industrial use - Chimphepo, L.; Monjerezi, M.; Alamu, Emmanuel Oladeji; Ntawuruhunga, P.; Saka, J.D.K. (Elsevier, 2022)
The study was carried out to evaluate the genotype by environment (G × E) interaction on physicochemical and functional properties of ten (10) cassava advanced genotypes and improved varieties. The genotypes and varieties were collected from a multi-location trial (Uniform yield) of the IITA breeding program at four research stations in Malawi. Based on the results, G × E interaction was highly significant (P ≤ 0.001) in explaining the variance of the physicochemical parameters and functional properties. Thus, G × E interaction highly influenced starch and amylopectin contents, swelling power, and water binding capacity. Additive main effect and multiplicative interaction (AMMI) analysis identified I010040, MM06/0045 and TMSL110080 genotypes and Mbundumali, Mpale and Sagonja varieties as the most stable with high yield performance hence recommended for cultivation in a wide range of environments for the production of high quality cassava flour (HQCF) and starch for various industrial applications such as the production of ethanol, biofuels, starch and glucose syrup in chemical industries; thickeners, stabilizers, and texture modifiers in food, bakery and confectionery industries.